Strengthening Bangladesh-Russia Relations for Sustainable Development: Challenges and Opportunities - Rahman, Md. Sayedur (Academia Journal of Humanities & Social Sciences, 2024)
At present, Bangladesh and Russia have a special relationship. It is proven that Russia is a tested and trusted friend of Bangladesh. From the very beginning of Bangladesh as an independent and sovereign state, Russia has always stood by its welfare and development. Establishing diplomatic ties since 1972, bilateral relations have not always been smooth due to a lack of political will, particularly during the martial law regime. There are many potential areas of cooperation that could prosper together if both friendly countries utilize them. This paper identifies several potential areas of mutual cooperation and argues that to attain sustainable development, Bangladesh-Russia relations need to be strengthened more and more. This study explores the potential areas through various channels for greater interest, friendship, and opening up a new era in bilateral issues. The study also looks into the challenges and opportunities for the Bangladesh-Russia economic partnership. It investigates issues related to trade barriers, infrastructure development, and energy cooperation. Additionally, this study examines the impact of political and diplomatic factors on the economic relationship between Bangladesh and Russia. The study is based on a combination of primary and secondary sources, including surveys with key stakeholders, economic data analysis, and a review of relevant literature.